ANALISIS PERSEPSI PROMOSI DAN KUALITAS PELAYANAN JASA MAKE UP ARTIST TERHADAP KEPUTUSAN PEMBELIAN - Wibowo, Zidan Febrianto; Sardanto, Rino (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This.study aims to analyze the factors that influence purchasing decisions using the dependent variable of promotion perception and service quality at Lian Make up Artist in Nganjuk. This research.uses.quantitative descriptive analysis method. The.research technique used in this study is causality by using.a.simple random sampling technique. The analytical tool used in this research is IBM SPSS. The results showed.that the promotion perception variable had a significant positive effect on purchasing decisions, while the service quality variable had no positive and significant effect on purchasing decisions. The novelty in this research is that the makeup provided by Lian Make up Artist is more modern and contemporary than its competitors. In addition, the promotions carried out are also different from their competitors, namely by giving bonus fees to anyone who brings new customers to Lian Make up Artist.